2022
DOI: 10.1007/s00464-022-09284-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience and prognostic factors of compensatory hyperhidrosis and recurrence after endoscopic thoracic sympathicotomy

Abstract: Objective We aimed to investigate compensatory hyperhidrosis (CH) and recurrence based on an online survey of patients who underwent endoscopic thoracic sympathicotomy(ETS) for palmar and/or axillary hyperhidrosis. Methods We enrolled 231 patients who underwent ETS for palmar and/or axillary hyperhidrosis from January 2008 to April 2021. Patients responded to an online questionnaire regarding CH and recurrence, their electronic medical records were reviewed. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…14 In contrast, a study by Woo et al, found a significant correlation between age over 20 years and the development of CH (OR: 2.73). 15 CH after botulinum toxin treatment was reported in a very small number of studies. A clinical trial that aimed to investigate the safety and efficacy of BTX-A in axillary hyperhidrosis mentioned that only 11 patients (5%) developed CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In contrast, a study by Woo et al, found a significant correlation between age over 20 years and the development of CH (OR: 2.73). 15 CH after botulinum toxin treatment was reported in a very small number of studies. A clinical trial that aimed to investigate the safety and efficacy of BTX-A in axillary hyperhidrosis mentioned that only 11 patients (5%) developed CH.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast, a study by Woo et al, found a significant correlation between age over 20 years and the development of CH (OR: 2.73). 15…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic sympathectomy and suction curettage may cause significant sweat reduction after 3−12 months 3–5 although suction curettage has proven inferior to botulinum toxin treatment 5 . However, compensatory hyperhidrosis in other body areas remains problematic 3,6 and the number of surgical corrections of PAH has declined over the last decade 7 . Iontophoresis and microneedle radiofrequency are not widely used for PAH due to fluctuating efficacy and the need for special equipment 8–10 .…”
Section: Introductionmentioning
confidence: 99%